Analisis Potensi Ekonomi Kabupaten Dan Kota Diprovinsi Daerah Istimewa Yogyakarta - Saputro, Deavid Ricard Pramesha, Dr. Daryono Soebagyo, M.Ec (2017)
The study was backed by the excellent potential of the phenomenon by the classification as well as the County/city in the Yogyakarta special region province have not been identified and utilized optimally for the development of construction.This study aims to determine and analyze the basic sectors with a competitive advantage and priority sectors for optimization bases in regional development. The Data used in this study is secondary data in the period 2011-2015 sourced from BPS regency / city and primary data sourced from Bappeda Province of DIY. The Analysis Model used the analysis of LQ, Shift-share and Analytical Herarchy Process (AHP). The results of this study concluded that the district / city have the potential to vary, the average, each district has three or more sectors of the base, while for the priority development of Bantul, Kulon Progo and Gunung Kidul in Agriculture, forestry and fisheries, Sleman regency in Tarnsportrasion and Warehousing sector also for the city of Yogyakarta in the Processing Industry sector.